2019
DOI: 10.1111/jpi.12587
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase 9 downregulation decreases tumor growth and promotes apoptosis in non‐small cell lung cancer after melatonin treatment

Abstract: Histone deacetylase 9 functions as an oncogene in a variety of cancers, but its role on non-small cell lung cancer (NSCLC) has not been reported. Melatonin was proven to possess anticancer actions, whereas its effect on NSCLC and underlying mechanisms remains poorly understood. In this study, 337 patients with complete clinicopathologic characteristics who underwent NSCLC surgery were recruited for the study. We found that NSCLC patients with high HDAC9 expression were correlated with worse overall survival an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 37 publications
3
37
0
Order By: Relevance
“…34 HDAC9 also acts as an oncogene in non-small-cell lung cancer. 35 In the present study, we confirmed that HDAC9 was the direct target gene of miR-30d-5p and that LOC440173 regulated HDAC9 expression in ESCC via competitively sponging miR-30d-5p. In addition, we used rescue assays to clarify the function of the LOC440173/miR-30d-5p/HDAC9 axis in ESCC progression.…”
Section: Discussionsupporting
confidence: 81%
“…34 HDAC9 also acts as an oncogene in non-small-cell lung cancer. 35 In the present study, we confirmed that HDAC9 was the direct target gene of miR-30d-5p and that LOC440173 regulated HDAC9 expression in ESCC via competitively sponging miR-30d-5p. In addition, we used rescue assays to clarify the function of the LOC440173/miR-30d-5p/HDAC9 axis in ESCC progression.…”
Section: Discussionsupporting
confidence: 81%
“…After the different treatments on H9c2 cells for 24 h, the cell viability was detected via using the CCK-8 kit (7Sea, Shanghai, China) according to the previously described [47]. Optical density (OD) values were measured at 450 nm through the microplate reader (SpectraMax 190, Molecular Device, USA).…”
Section: Methodsmentioning
confidence: 99%
“…8,9 It is involved in sleep and circadian rhythms, antioxidant activity, and immunity enhancement. 10 In addition, melatonin is regarded as a multifunctional oncostatic agent 11,12 and is potentially therapeutic for nonsmall cell lung cancer, 13 colorectal cancer, 14 Alzheimer's disease, 15 chronic kidney disease, 16 and acute ischemia-reperfusion liver injury. 17 Notably, some studies have showed that melatonin is involved in reproduction, fertility, and development.…”
mentioning
confidence: 99%